Semantic development and its effect on meaning orientation in simple tafsir by al-Wahidi al-Nisaburi (d. 468 AH) - Hneehin, Dr. Hamid Hussein (Thi Qar Arts Journal, 2021)
The phenomenon of semantic development predominates in all human languages ​​without exception, as this phenomenon does not pertain to one language without the other, and Arabic does not include all of it. And upon the advent of Islam and the revelation of the Noble Qur’an, the development and change of the words of the Arabic language took place. Therefore, these papers came in an attempt to trace that phenomenon that was known in the researches of linguists as the phenomenon of semantic development in language utterances. The research stands on this phenomenon in a simple explanation, was the title is: development of semantic in Albesatootherh interpretation in guiding sense, guarantees the research in preparation explained the meaning of the semantic development of the language and idiomatically, and admonishing three first: in the allocation of significance Baadalatsaa, and the second in the mainstream connotation of words after The specification, and the third: in the transition of the field of semantics, and finally the conclusion that included the results of the research.